2017
DOI: 10.15809/irriga.2017v22n3p443-457
|View full text |Cite
|
Sign up to set email alerts
|

Balanço Hídrico Em Função De Regimes Pluviométricos Na Região De Petrolina-Pe

Abstract: RESUMOO estudo das condições climáticas da região de Petrolina se faz necessário devido sua importância no cenário agrícola nacional. O objetivo do trabalho foi caracterizar os perfis pluviométricos, classificar por meio da utilização de técnica quantílica e a realização de balanço hídrico para diferentes regimes hídricos observados. Foram utilizados da estação meteorológica convencional (OMM: 81991) localizada no município de Petrolina-PE, os dados de precipitação pluvial e temperatura média do ar condensada.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 5 publications
0
13
0
8
Order By: Relevance
“…Field sampling was carried out in the second half of 2016, a period of extreme water deficit in the region (LOPES et al, 2017;LOPES et al, 2018), which can be confirmed by the precipitation of the previous year and by the historical data series of 1990-2016 ( Figure 1).…”
Section: Area Descriptionmentioning
confidence: 84%
“…Field sampling was carried out in the second half of 2016, a period of extreme water deficit in the region (LOPES et al, 2017;LOPES et al, 2018), which can be confirmed by the precipitation of the previous year and by the historical data series of 1990-2016 ( Figure 1).…”
Section: Area Descriptionmentioning
confidence: 84%
“…The five sequential applications of Gelsura™ at seven-day intervals starting at 35 days prior to harvesting at the beginning of the infestations maintained the infestation of medfly adults at lower or equal levels relative to the Success™ 0.02 CB, and at levels equal or less than the conventional management with or without sprays (control). One variable to be evaluated in future studies is an increase in the interval between applications because in this region precipitation is low (Lopes et al 2017). However, due to the incident sunlight, there may be greater degradation of the active ingredient, and this should be quantified to enhance the effectiveness of the applications (Allen et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Também, o tipo de sistema de irrigação pode influenciar nos aspectos bioquímicos e fisiológicos da planta. Em sistemas por gotejamento a aplicação de água é mais próxima ao sistema radicular, e nesse cenário a planta gasta menos energia em busca de água e nutrientes, direcionando esse esforço para a sua produção (COELHO et al, 2001;TAIZ & ZEIGER, 2017 como BSwh, por Köppen, apresentando os maiores picos entre outubro e dezembro, enquanto julho é o mês mais frio (LOPES et al, 2017). A classificação textural do solo da área é arenosa, conforme observado na tabela 1.…”
Section: Fundamentação Teóricaunclassified
“…Nesse contexto, estudos têm demonstrado a viabilidade socioeconômica do cultivo da pereira no Vale do Submédio São Francisco, utilizando cultivares que requerem poucas horas de frio para superar essa fase de dormência (LOPES et al, 2013). Nessa região a exploração de algumas plantas cultivadas só é possível em função da técnica da irrigação devido, principalmente, a fatores climáticos como altas temperaturas, baixa umidade relativa do ar e má distribuição de chuvas (LOPES et al, 2017).…”
Section: Introductionunclassified